Análisis de la inversión no financiera del Gobierno Regional de Loreto en la región Loreto, periodo 2012 - 2016 - Bendezú Delgado, Roberto Alonzo (2018)
The investigative research in this thesis is about the behavior of the nonfinancial inversions made during the 2012- 2016 period, in which the sources of income will be identified and the destiny of these within the different productive sectors of the Loreto region. However, we will briefly review the background and events that occurred and had a negative impact on the development and economic growth of the Loreto region, as well as explain the importance of the intervention of the central government through public investment to counteract the effect of the events of a political nature that affected the state investment projects aimed at the social welfare. Likewise, we will emphasize the value represented by the capacity to manage public funds and the provision of sufficient resources associated with reasonable economic and political strategies for the efficient execution of necessary projects aimed at improving infrastructure and consequently the quality of life. In addition, based on a specific analysis of the educative and health sectors, we will discover the origin and influence of the inversion made by the state in these sectors are the most active in the economic flow of the Loreto region. Finally, we manifest how important the non-financial inversions were during the mentioned period for the economic growth and social development in the region.